Dynamic performance and optimization of locomotives with elastic suspension on bogie frames and permanent magnet direct drive - QIAO Jinchuang; HE Xing; WANG Zhiming; YAO Yuan (机车电传动)
This paper delves into the dynamic performance of six-axle freight electric locomotives featuring elastic suspension on bogie frames and permanent magnet direct drive. Simulation calculations based on SIMPACK software examined locomotive dynamics, focusing on their lateral stability, straight line operating performance, and curve negotiation safety. Subsequently, the calculation results were compared with those of traditional locomotives equipped with axle suspension and gear drive. The comparison results showed that, except for improvement in wear performance at the flange and tread of the leading wheelsets on curves with a small radius, the lateral dynamic performance of locomotives featuring suspension on bogie frames and direct drive, exhibited no obvious advantage over gear-driven locomotives, particularly in straight-line scenarios. This is attributed to the large inter-spring mass and yawing inertia of bogies with frame suspension and direct drive, which contribute to the lack of lateral stability in these locomotives. Consequently, an improvement solution was proposed that incorporates an additional anti-yaw damper. The calculation results show enhanced performance in the lateral dynamics of locomotives operating on straight tracks, with performance indexes comparable to those of gear-driven locomotives.